Accuracy of multiple implant impressions using different combinations of impression materials using closed tray technique: An in vitro study - Madhura Deshmukh; Nabeel Ahmed; Subhabrata Maiti; Vaishnavi Rajaraman (Wolters Kluwer Medknow Publications, 2022)
Decision for precision! The first stage in creating an accurate, passively fitting prosthesis is to replicate the intraoral relationship of implants using impression methods. The technique and the impression material utilized are the key elements that influence the accuracy of the implant imprint. The goal of this study was to assess the accuracy of the described implant impression technique using various impression materials, as well as to look into the clinical aspects that influence implant impression accuracy. Two holes (4.3 mm × 10 mm) were drilled in a U-shaped study plastic model representing the partially edentulous maxilla, and the appropriate Nobel Biocare Replace select implants were implanted. Closed tray copings were placed for the relevant implants, and closed tray impressions were taken with several impression materials (PVS-1) Dentsply, medium-bodied, and 2) Regular setting-Zhermack Elite HD+). To assess passive fit accuracy, a jig trial and RVG IOPA were used. Stereomicroscopy was used to evaluate the precision of the implant and analog interface from two perspectives: buccal and lingual. On the buccal aspect, Group 1 had a mean value of 13703.29, whereas Group 2 had a mean value of 11395.58. On the lingual aspect, Group 1's mean value was 8415.61, whereas Group 2's was 9192.01. In the closed tray technique, no statistically significant differences between different imprint materials were found. There was no significant difference in the accuracy of closed tray implant impression techniques with different impression materials, according to the findings.